Trends in private investment in developing countries statistics for 1970-1998 - Bouton, Lawrence; Bouton, Lawrence; Sumlinski, Mariusz A. (Washington, D.C. World Bank, 2000)
Annotation International Finance Corporation Discussion Paper no. 41. While theoretical growth models developed in the economics literature make no distinction between private and public components of investment, there is an emerging appreciation that private investment is more efficient and productive than public investment. Results from the recent empirical literature, updated here with the recent data on private investment, suggest that private investment has a stronger association with long run economic growth than public investment. The role of private investment in economic growth is examined in the first part of this discussion paper. The second part shows trends in private and public fixed investment in fifty developing countries.
Keywords: Investments -- Developing countries -- Statistics; Investments, Foreign -- Developing countries -- Statistics